The Optimization of Collimator Material and In Vivo Testing Dosimetry of Boron Neutron Capture Therapy (BNCT) on Radial Piercing Beam Port Kartini Nuclear Reactor by Monte Carlo N-Particle Extended (MCNPX) Simulation Method - Yohannes Sardjono; Kusminarto Kusminarto; Ikna Urwatul Wusko (Indonesian Journal of Physics and Nuclear Applications, 2018)
Boron Neutron Capture Therapy (BNCT) on radial piercing beam port Kartini nuclear reactor by MCNPX simulation method has been done in the National Nuclear Energy Agency Yogyakarta. BNCT is a type of therapy alternative that uses nuclear reaction 10B (n, α) 7Li to produce 2.79 MeV total kinetic energy. To be eligible IAEA conducted a study of design improvements and variations on some parameters to optimum condition which are Ni-nat thickness of 1.75 cm as collimator wall, Al2S3 as thick as 29 cm as moderator, Al2O3 0.5 cm thick as filter, Pb and Bi thickness of 4 cm as the end of the gamma shield collimators and Bi thickness of 1.5 cm as the base gamma shield collimators. The total dose was accepted in the tumor tissue 900 × 10-4 Gy/s. Radiation dose on the tumor tissue is 50±3 Gy with time irradiation of 9 minutes and 10 seconds. That dose was given into skin tissue and healthy liver tissue consecutively (6.00±0.05) × 10-2 Gy and (10.00±0.05) × 10-2 Gy. It shows the dose received by healthy tissue is still within safe limits.